PENGARUH GAYA KEPEMIMPINAN SINGA AMBARA RAJA, DISIPLIN DAN PELATIHAN TERHADAP KINERJA PEGAWAI PADA DINAS PARIWISATA KABUPATEN BULELENG - WIDYANINGRUM, A.A. AYU MAHAYUNI; GAUTAMA, ANAK AGUNG NGURAH RESTU; RIANITA, NI MADE (Ganec Swara, 2025)
This research aims to determine the influence of the leadership style singa ambara raja, discipline and training on employee performance at the Buleleng Regency Tourism Office. The data analysis techniques used in this research are multiple linear regression analysis, classical assumption testing, goodness of fit testing, hypothesis testing using the SPSS Version 21.0 for Windows application. The results of this research show that the leadership style singa ambara raja has a positive and significant effect on the performance of the Buleleng Regency Tourism Office employees. This indicates that the better the leadership style of the leader in directing employees at work, the greater the resulting performance. Discipline has a positive and significant effect on the performance of Buleleng Regency Tourism Service employees, this indicates that the better the employee's discipline, the more the employee's performance will increase, in this case the discipline possessed by Buleleng Regency Tourism Service employees greatly influences employee performance. Training has a positive and significant effect on the performance of Buleleng Regency Tourism Office employees, this indicates that the more frequently employees attend training, the more influence it will have on the resulting performance. Based on the results of the f test, it is known that the value of F-count > F-table, (37.469 > 3.21), this indicates that the variables of leadership style singa ambara raja, discipline and training have a joint effect on the performance of employees at the Buleleng Regency Tourism Office at a level significant 0.000 < 0.050.